Combination administration of alprazolam and N-Ethylmaleimide synergistically enhances sleep behaviors in mice with no potential CNS side effects - Siqing Zhu; Jingjing Shi; Yi Zhang; Xuejun Chen; Tong Shi; Liqin Li (PeerJ, 2024)
Background N-Ethylmaleimide (NEM), an agonist of the potassium chloride cotransporters 2 (KCC2) receptor, has been correlated with neurosuppressive outcomes, including decreased pain perception and the prevention of epileptic seizures. Nevertheless, its relationship with sleep-inducing effects remains unreported. Objective The present study aimed to investigate the potential enhancement of NEM on the sleep-inducing properties of alprazolam (Alp). Methods The test of the righting reflex was used to identify the appropriate concentrations of Alp and NEM for inducing sleep-promoting effects in mice. Total sleep duration and sleep quality were evaluated through EEG/EMG analysis. The neural mechanism underlying the sleep-promoting effect was examined through c-fos immunoreactivity in the brain using immunofluorescence. Furthermore, potential CNS-side effects of the combination Alp and NEM were assessed using LABORAS automated home-cage behavioral phenotyping. Results Combination administration of Alp (1.84 mg/kg) and NEM (1.0 mg/kg) significantly decreased sleep latency and increased sleep duration in comparison to administering 1.84 mg/kg Alp alone. This effect was characterized by a notable increase in REM duration. The findings from c-fos immunoreactivity indicated that NEM significantly suppressed neuron activation in brain regions associated with wakefulness. Additionally, combination administration of Alp and NEM showed no effects on mouse neural behaviors during automated home cage monitoring. Conclusions This study is the first to propose and demonstrate a combination therapy involving Alp and NEM that not only enhances the hypnotic effect but also mitigates potential CNS side effects, suggesting its potential application in treating insomnia.